Vous êtes sur la page 1sur 15

 

             

 

 

 
 

 

 

 

↑ ↓

 

 

 

π

a b c

ax 2 + bx + c = 0

(x) =

i=0

x i

i!

n + 1

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

A =

4

3

π/4 , B =

5

2

72/3

3 + i

0.2

i

A + B, AB, A 2 , A T , B 1 , B T A T , A 2 + B 2 AB

Ax = b

A

5x + 6y + 10z

=

4

3x + 14z

=

10

7y + 21z

=

0

x 4 12x 3 + 5x

 

y(x) = e 0.8x ωx

ω = 10 x [0 10]

ω = 1, 3, 10 x [0 5] ω = 1 ω = 3 ω = 10

y(x) = 10 + 5e x (ωx + 0.5)

dy 1

dt

dy 2

dt

dy 3

dt

= y 2 y 3

= y 1 y 3

= 0.51 y 1 y 2

y 1 (0) = 0 y 2 (0) = 1 y 3 (0) = 1

 

dx

1

dt

dx

2

dt

=

x 2

= ω(1 x 2 )x 2 ω 2 x 1

1

t [0 100] x 1 (t) ω = 1 = 0.1 x 1 (0) = x 2 (0) = 0

y = (x(1) t)

(x(n) t)